Physicamente vigorosos: medicalização escolar e modelação dos corpos na Paraíba (1913-1942) - Soares Júnior, Azemar dos Santos (2015)
This thesis aims to analyze the construction of the physically strong children body from medical-pedagogical discourses facing schools of Paraíba between 1913, the year of implementation of the courses of Hygiene and Physical Education in School Program of two private schools - College Nossa Senhora das Neves and the Diocesan College Pius X - and a military public school - Seaman Beginners School -; and 1942, year of the last publication of the Education Magazine, pedagogical resource that sustained the circulation of the medical knowledge focused on teacher training. During the research I came across a vast document collection, which, after a process of selection and analysis, allowed the writing of a story filled with norms and codes to civilize, bodies that hygienized and exercised, which aspired strong and health. To discuss these bodies, it was necessary to visit newspapers, magazines, regulations, laws, decrees, letters, almanacs, textbooks, memory books, photographs, immunization cards, medical notes, manuscripts, among others. Along the way, we draw the following thesis argument: the manufacture of medical and educational projects aimed at intervening in school, shape it, form it hygienically. To do this, it was set a discourse on the several fields that form the school: the building, teachers, students, standards. In an attempt to instill the precepts of hygiene in vogue, physicians stepped into the schools, rested on them speeches and actions that that can serve their interests. Thus, they passed to realize lots of teacher trainings and created several forms of circulating the medical knowledge to teachers. A project that involved three segments: the physicians, the standard creators, teachers who received the rules and we were responsible to expose them and the students who received such precepts and should put it into practice. It is not possible to affirm that the project which aimed to discipline bodies and minds of children in Paraíba schools was victorious, but it was possible to analyze from Michel Foucault's contributions on the subject. The standards were created, most of them by the State and imposed to teachers and students, most of them at the base of imposition, of something that must be done. In Paraíba, the project had the leadership of the health officer doctor Flávio Maroja, who joined forces to undertake a collective, national project, in line with those developed in the Federal Capital and in other states. So, constantly receiving new rules that should be defended: the rules of school hygiene, care of the architecture of the buildings, body cleaning, Swedish gymnastics, the various forms of exercise the body, among them the scouting and the soccer and the textbooks that served as conduits of a hygienic awareness. All of these are elements of a project that climbed body the order construction, obedient, strong, beautiful and healthy.